Leading inclusively, thriving resiliently: Testing a mediation–moderation model of employee well-being in the retail industry - Fithriyah, Dian Faza; Pareke, Fahrudin JS (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
The present study examined the impact of inclusive leadership on employee well-being, with psychological resilience serving as a mediating variable and perceived organizational support as a moderating variable. The participants were employees of a retail chain in Bengkulu, Indonesia. A total of 220 respondents were surveyed using an online, structured questionnaire with a six-point Likert scale. Data analysis was conducted using partial least squares structural equation modeling (PLS-SEM) in SmartPLS 4.0. The study’s findings demonstrate that inclusive leadership positively and significantly influences employee well-being and psychological resilience. Furthermore, psychological resilience has been shown to enhance employee well-being and in mediate the association between inclusive leadership and well-being. However, perceived organizational support did not demonstrate a statistically significant moderating influence on the connection between psychological resilience and employee well-being. Theoretically, this research contributes to prior scholarship by clarifying the processes by which inclusive leadership enhances employee well-being through the development of psychological resilience. From a pragmatic standpoint, the present results highlight the necessity of fostering inclusive leadership and reinforcing psychological resilience initiatives in the retail industry. Additionally, the findings indicate that the perceived role of organizational support can vary contingent upon the organizational context and culture.